Education and Empowerment of Women: Issues and Impact: Exploring the Link between Women's Education and Empowerment (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Empowerment of women is a necessity for the development of a society, because it improves both the quality and quantity of individual resources available for development. It is one of the major practical concerns when concentrate on human right and development. Women empowerment is essential for our society to ensure the sustainable development of the country. Without the empowerment of women, it would be a fable to dream about the target of sustainable development. Women contribute almost half of the population and empowered women will strengthen the national economy. Education is one of the key aspects that enable the women to respond to the challenges, to confront the traditional role and change their lives. Education has also been considered as a key to unlock the golden door of freedom for the development. Education helps in reducing inequalities and function as a means of improving the status of women within the family and society. Empowering women provides an opportunity to acquire practical information and learning for their improved livelihoods. Our country can become a developed nation only if large women folk contribute the best of her ability and capacity which is possible when she is empowered and educated. This paper will discuss the role of education and its impact in empowerment of women and challenges that come in the pathway.